2019
DOI: 10.1002/hfm.20793
|View full text |Cite
|
Sign up to set email alerts
|

Hand as hammer: A comprehensive review of biomechanical studies related to occupational hand strikes

Abstract: A growing number of workers in modern automotive assembly plants are confronted with occupational tasks involving repeated high-impact hand strikes. Such repetitive physical workloads account for diseases of soft tissues or musculoskeletal disorders in the hand, wrist, or entire upper body. The purpose of this review was to identify and discuss the most pertinent occupational and physiological investigations concerning such hand strikes with particular emphasis on the biomechanical parameters examined. Article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Its use is in self-defense without any protective equipment and according to the type of strike also in specific combat sports such Kyokushin karate [ 27 ], Mixed Martial Art [ 28 ], Muay Thai [ 29 ]. After the impact of the punch, the force is applied for a short period of time [ 30 ] (less than 50 ms with time to peak 5.08 ± 0.57 ms) [ 31 ] as the product of high mass and acceleration just before the impact [ 32 ]. The speed before the impact is the decisive factor determining the impact force [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its use is in self-defense without any protective equipment and according to the type of strike also in specific combat sports such Kyokushin karate [ 27 ], Mixed Martial Art [ 28 ], Muay Thai [ 29 ]. After the impact of the punch, the force is applied for a short period of time [ 30 ] (less than 50 ms with time to peak 5.08 ± 0.57 ms) [ 31 ] as the product of high mass and acceleration just before the impact [ 32 ]. The speed before the impact is the decisive factor determining the impact force [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is useful to know other variables, such as the striking area of the upper limb, for pressure calculation, potentially leading to alternative head injury assessment compared to the standard peak force criterion [ 35 ]. Previous studies [ 30 , 32 ] show that, in addition to the standard variables, the description of the strike area is not sufficiently addressed even though it may have a major impact on the interpretation of interactive forces and pressures developed in strikes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the results were not put in the context of biomechanical parameters, such as muscle activity. Other studies found that fist strikes, compared with palm strikes, show increased peak stresses, higher effective mass, and smaller peak acceleration and impulse (Hausmanninger et al, 2019). High acceleration values in palm strikes are described as a risk factor for progressing stress in hand surfaces and soft structures (Cochran et al, 2006).…”
mentioning
confidence: 98%